An Update on Solubility Enhancement Methods for BCS Class -II Drugs - Vamshi Krishna Tippavajhala (Journal of Global Pharma Technology, 2017)
Abstract: To attain the anticipated concentration of a drug in the systemic circulation in order to exhibit the pharmacologic response, solubility of the drug plays a critical role. Key research problems faced during formulation development of various drugs owe to their low aqueous solubility. About 40% of NCEs are unsuccessful in reaching their therapeutic range mainly due to their solubility issues. In this context, this review article details various solubility enhancement techniques and their application mainly to address this poor solubility of various BCS class-II drugs. Keywords: Solubility Enhancement Methods, BCS Class-II drugs.